Archaeology of the recent: Wooden artefacts from Anbangbang 1 and Djuwarr 1, western Arnhem Land. Issue 2 (3rd May 2020) - Allen, Harry; Brockwell, Sally
Abstract: In 1985, Annie Clarke analysed botanical materials from Anbangbang 1 and Djuwarr 1, Kakadu National Park, western Arnhem Land. The 49 wooden artefacts from Anbangbang 1 and 20 wooden artefacts from the Djuwarr 1 site in Deaf Adder Gorge are now in the collections of the Museum and Art Gallery of the Northern Territory (MAGNT). This research involves a re-examination of these artefacts in terms of their morphological and functional attributes. They are interpreted within the context of ethnographic observations and information from Arnhem Land archaeological sites of a comparable age, particularly those combining archaeology with rock art research. The study shows convergence between the archaeology, rock art and ethnography, indicating the importance of spears in the life of Aboriginal people, in this case reed spears and spears with barbed heads. The study also documents variability as regards seasonality of site use and hunting patterns in response to environmental changes around 1, 500 BP.